2012
DOI: 10.1021/ol303105d
|View full text |Cite
|
Sign up to set email alerts
|

Diastereo- and Enantioselective Asymmetric Hydrogenation of α-Amido-β-keto Phosphonates via Dynamic Kinetic Resolution

Abstract: Dynamic kinetic resolution of various α-amido-β-keto phosphonates via asymmetric hydrogenation proceeded efficiently to give the corresponding β-hydroxy-α-amido phosphonates in high diastereo- and enantioselectivities (up to 99:1 syn/anti, 99.8% ee). The addition of catalytic amounts of CeCl(3)·7H(2)O is necessary to achieve both good selectivity and catalytic efficiency under mild reaction conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(13 citation statements)
references
References 54 publications
0
13
0
Order By: Relevance
“…In 2013, Zhang and co-workers reported a convenient and general protocol for the synthesis of these compounds through Ru-catalyzed hydrogenation of α-amido β-keto phosphonates via DKR (Scheme 13). 29 By using [RuCl(benzene)(S)-SunPhos]Cl as the catalyst, excellent levels of stereoselectivity were observed for the corresponding syn-α-amido β-hydroxy phosphonates (up to 99:1 syn/anti, up to 99.8% ee). The authors demonstrated the crucial role of additives in the stereochemical outcome of the reaction, because a dramatic increase of both dr and ee was observed after the addition of CeCl 3 •7H 2 O.…”
Section: α-Substituted β-Keto Phosphonates and Sulfonesmentioning
confidence: 99%
“…In 2013, Zhang and co-workers reported a convenient and general protocol for the synthesis of these compounds through Ru-catalyzed hydrogenation of α-amido β-keto phosphonates via DKR (Scheme 13). 29 By using [RuCl(benzene)(S)-SunPhos]Cl as the catalyst, excellent levels of stereoselectivity were observed for the corresponding syn-α-amido β-hydroxy phosphonates (up to 99:1 syn/anti, up to 99.8% ee). The authors demonstrated the crucial role of additives in the stereochemical outcome of the reaction, because a dramatic increase of both dr and ee was observed after the addition of CeCl 3 •7H 2 O.…”
Section: α-Substituted β-Keto Phosphonates and Sulfonesmentioning
confidence: 99%
“…When α‐methylene was substituted with Me, Et, or Br, high ee values and syn / anti ratios were observed ( 14k – m ). Moreover, in the presence of CeCl 3 •7H 2 O, and under otherwise the same reaction conditions, highly diastereo‐ and enantioselective hydrogenation of α‐amido‐β‐keto phosphonates was realized through dynamic kinetic resolution (DKR; Scheme ) 30…”
Section: β‐Functionalized Ketonesmentioning
confidence: 99%
“…Cerium chloride heptahydrate (CeCl 3 · 7H 2 O), the most common commercially available source of Ce +3 , finds useful application as a catalyst in heterocyclic synthesis. 31 It is a mild Lewis acid which has low toxicity and is relatively inexpensive. Hence, it is a good candidate for green organic transformations.…”
Section: Introductionmentioning
confidence: 99%